S.T.O.R.I.A. Storytelling and Technology Outreach for Reviving Indigenous Arabic - Saad, Sharina; Subri, Shafilla; Abdul Aziz, Anis Aisyah; Tengku Mahazir, Tengku Aina Munirah; Zuhaidy, Muhammad Uzair; Kamarul Zaman, Muhammad Zaid (2025)
S.T.O.R.I.A. (Storytelling and Technology Outreach for Reviving Indigenous Arabic) is an innovative digital learning solution designed to integrate language acquisition with cultural preservation. This project combines authentic Semai oral narratives with Arabic language instruction in an immersive audiobook format. The intervention addresses the limited availability of engaging, culturally relevant resources for non-native Arabic learners while promoting respect for indigenous heritage. A Semai folktale titled The Rules of The Jungle was selected, translated, and enriched with targeted Arabic vocabulary. Professional narration, sound design, and visual aids were developed to create a multimedia experience accessible on mobile devices. Learners participated in a four-week program involving listening sessions, interactive tasks, and reflection activities. Pre- and post-intervention assessments measured vocabulary retention, motivation, and learner perceptions. The results demonstrated significant improvements in vocabulary recall and sustained motivation to learn Arabic. Learners also reported a deeper emotional connection to the stories, which enhanced engagement and cultural awareness. These findings align with previous research highlighting the effectiveness of digital storytelling in language education. S.T.O.R.I.A. demonstrates that culturally integrated, technology driven tools can make language learning more meaningful, inclusive, and sustainable. This model offers strong potential for adaptation to other languages and contexts, creating a valuable resource for educators and learners committed to preserving cultural identity while advancing linguistic competence.